Connected Health 2016: Emotion Sensing, the Next Big Trend? - Czerwinski, Mary (Connected Health 2016, 2016)
Panel: Emotion Sensing, the Next Big Trend? Wearable sensors know when we're happy or what makes us sad. Tracking breathing patterns, heart rate, brain waves, sweaty palms and even facial expressions, these devices have the potential to positively impact mood, stress levels and even promote healthy behaviors. From the clinic to the classroom to home, how will emotion sensing technology be used to improve health and wellness? Moderator: Jennifer Joe, MD, CEO, Medstro.com; Editor-in-Chief, MedTechBoston.com, @JenniferJoeMD Panelists: Mary Czerwinski, Research Manager, Microsoft Research, @Czerwinski Gabi Zidjerveld, Chief Marketing Officer, Affectiva Kristin Neidlinger, Concept Design Lead, SENSOREE Therapeutic Biomedia